55.4k views
0 votes
Solve 2(x + 3) = -4(x + 1) for x.

User ClintL
by
5.0k points

2 Answers

3 votes
X= -1.6 , X=-5/3 , or X= - 1 2/3
1 vote

Answer:

x = -10/6 or - 5/3 (in lowest terms)

Explanation:

To solve 2(x + 3) = -4(x + 1) for x:

Distribute 2 into (x + 3), and -4 into (x + 1):

2(x + 3) = -4(x + 1)

2x + 6 = -4x - 4

Add 4x to both sides:

2x + 6 + 4x = -4x + 4x - 4

6x + 6 = -4

Subtract 6 from both sides:

6x + 6 - 6 = -4 - 6

6x = -10

Divide both sides by -6:


(6)/(6) = (-10)/(6)

x = -10/6 or - 5/3 (in lowest terms)

User Macki
by
4.7k points